(untitled) (Cadernos de Sociomuseologia, 2015)
This work defends the hypothesis that the places of memory involving political issues should be dealt with using a processual museological approach so that they will play a contemporary social role in society. The sociomuseological approach is fundamental in the concept and the application of the idea, which presupposes a political commitment and collective construction by the social actors and professionals from various disciplines and areas of expertise. The sociopolitical and cultural contexts are discussed, and a conjugation of three factors is espoused for the effective creation of these institutions: demands by the communities, willingness on the part of government, and museological action. From a processual perspective, the conception of the museological project, of the museological plan, and of the strategic planning is fundamental for the institution‟s development, as these are the guiding documents. The dissertation takes as a case study the Memorial da Resistência de São Paulo (Memorial to the Resistance of São Paulo), situated in part of the building that belonged to the Departamento Estadual de Ordem Política e Social de São Paulo (State Department of Political and Social Order of São Paulo – Deops/SP), and which preserves the memories of the resistance and political repression of Republican Brazil (since 1889) by means of the musealization of the prison space and the development of programmatic lines of action, seeking to collaborate toward the improvement of democracy and of a culture of human rights. Keywords: Places of Memory; Sociomuseology; Musealization; Museological Process; Memorial da Resistência de São Paulo.